أهمية المعاينة الاحصائية في عملية المراجعة - louglaithi, lakhdar; Ben dakfel, Kamel; Bentirache, Atallah (Finance and Business Economies Review, 2018)
The statistical inspection is one of the most important tools used by the auditor as it contributes to the performance of the review process. This is due to the large volume of accounting operations and their complexity. Therefore, it is necessary to rely on statistical sampling method which depends on the selection of samples from the accounting operations community in order to detect, correct and fix errors in the shortest time and at the lowest cost.